2020
DOI: 10.22219/jpbi.v6i2.12236
|View full text |Cite
|
Sign up to set email alerts
|

Integrated STEM-based module: Relationship between students’ creative thinking and science achievement

Abstract: STEM-based learning innovations have been massively developed especially related to 21st Century skills. This study was done to explore a relationship between creative thinking and science achievement through the implementation of integrated STEM-based module on Reproduction topic. A quasi-experimental study involved pretest-posttest non-equivalent group design with sample of 60 eighth graders from a boarding school in Baling, Kedah, Malaysia. The samples was divided into two groups - 30 students of treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
1
7
0
1
Order By: Relevance
“…Research conducted by Ulfa (2021) using STEM integrated physics module improves student learning outcomes in cognitive aspects. STEM-integrated e-modules provide significant results for students' critical thinking skills in science learning and STEM integration combines real concepts in learning so as to enable students to be able to compete in the new era (Shukri, 2020;Hasanudin et al, 2022). Based on previous researchers, it was concluded that the use of STEM integrated physics emodules can improve student learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by Ulfa (2021) using STEM integrated physics module improves student learning outcomes in cognitive aspects. STEM-integrated e-modules provide significant results for students' critical thinking skills in science learning and STEM integration combines real concepts in learning so as to enable students to be able to compete in the new era (Shukri, 2020;Hasanudin et al, 2022). Based on previous researchers, it was concluded that the use of STEM integrated physics emodules can improve student learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…STEM-based learning can also develop the scientific skills of students (Sahin et al, 2014;Sutaphan & Yuenyong, 2019;Thomas & Watters, 2015). Moreover, metacognitive skills and creative thinking can be empowered by learning on a STEM basis (Mariano et al, 2021;Pollard et al, 2018;Santangelo et al, 2021;Shukri et al, 2020). Therefore, the results from this research can become the basis for applying STEM-based learning in education, especially in remote learning, so that students can cultivate meaningfulness in learning and empower higher-order thinking skills.…”
Section: Introductionmentioning
confidence: 79%
“…Creative thinking skills may explain the causal relationships of events that occur around them (Felder & Brent, 2016;Shukri et al, 2020). Creative thinking skills will be more easily empowered if students have good metacognitive abilities.…”
Section: First Stage: Definementioning
confidence: 99%
See 1 more Smart Citation
“…Also, the globalization era promotes students to apply knowledge through problem-solving and appropriate collaboration (Koh et al, 2010;Maas et al, 2018;Sturner et al, 2017). 21 st -Century learning needs to center on thinking and collaboration skills (Shukri et al, 2020). Collaboration skills are an interpersonal arrangement that is more than just cooperation (Davidsen et al, 2020;Neubert et al, 2015).…”
Section: Introductionmentioning
confidence: 99%